Histogenesis of human fetal liver from 12 weeks to 36 weeks of gestation - Ch., Farhat Subhaana; Talapala, Venkata Ramani; Seethamsetty, Saritha (International Journal of Research in Medical Sciences, 2020)
Background: Fetal human liver developmental morphology is very important for diagnosis of congenital anomalies. The development of human liver is an ongoing process which begins after fertilization and continues into post-natal life. Liver is one of the organs of gastrointestinal tract having both exocrine and endocrine functions and capable of regeneration. Not only adult liver, the fetal liver is also an important organ with Haemopoietic functions. Pediatric liver transplants accounting for 10-15% of all liver transplants worldwide occur due to congenital defects. Methods: The study is conducted on 50 livers procured from 50 aborted fetuses (34 males and 16 females) ranging from 12 to 36 weeks of gestation .After confirming their age through CRL they were grouped. Then processed to form sections and stained with hematoxylin and eosin and seen under light microscope. Results: Histogenesis and development of human liver in prenatal period was observed under the microscope at various gestational age groups which was confirmed with lobular pattern, portal triad structures ,central vein and sinusoids showing fetal haemopoietic function which regress towards the term. Conclusions: The present study gave emphasis on all physical parameters and a detail histogenesis and development of human liver in prenatal period from 12 to 36 weeks of gestation. This work agreed with previous studies.